NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN DETERMINATION IN CARDIOVASCULAR DISEASES - Bilovol, O.M.; Kniazkova, I.I.; Tveretinov, O.B.; Kopytsya, M.P.; Kuzminova, N.V.; Kondrusyk, N.Yu.; Abramova, L.P. (World of Medicine and Biology, 2024)
Previous studies of neutrophil gelatinase-associated lipocalin levels have focused on studying its changes in various pathological conditions. These studies have demonstrated the high sensitivity of this marker in tubulointerstitial kidney injury. The aim of the work was to study the current state of the diagnostic and prognostic significance of the neutrophil gelatinase-associated lipocalin biomarker in cardiovascular diseases according to experimental and clinical investigations. An analysis of literary sources from the Pubmed and Web of Science databases over the last 5 years was conducted. It has been established that neutrophil gelatinase-associated lipocalin deficiency contributes to the development of atherosclerotic changes in vessels in the initial stages of the disease and accelerates the progression of atherosclerosis. A significant increase in serum neutrophil gelatinase-associated lipocalin levels has been noted in patients with angiographically confirmed ischemic heart disease and the number of affected vessels. Increased neutrophil gelatinase-associated lipocalin expression has been identified in hypertension and heart failure, but the pathogenetic mechanisms of these changes continue to be studied. Elevations of this biomarker in the blood are associated with adverse early and long-term outcomes in acute myocardial infarction and heart failure.
Keywords: neutrophil gelatinase-associated lipocalin; lipocalin 2; ischemic heart disease; arterial hypertension; myocardial infarction; heart failure; prognosis